The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12884-021-03565-3
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a modified World Health Organization safe childbirth checklist in health centers of Ethiopia: a pre and post intervention study

Abstract: Background Childbirth is a complex process, and checklists are useful tools to remember steps of such complex processes. The World Health Organization safe childbirth checklist is a tool used to improve the quality of care provided to women giving birth. The checklist was modified by Ministry of Health and was introduced to health centers in Ethiopia by the USAID Transform: Primary Health Care Activity. Methods A pre and post intervention study des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Similarly, a pre and postintervention study conducted in Ethiopia on SCC implementation found a 26.2% improvement in EBPs at this pause point. 38 Thus, this positive impact of the checklist on neonatal care denotes the importance of this tool for reducing early neonatal mortality, 11 17 18 which showed the slowest improvement during the era of the Millennium Development Goals. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a pre and postintervention study conducted in Ethiopia on SCC implementation found a 26.2% improvement in EBPs at this pause point. 38 Thus, this positive impact of the checklist on neonatal care denotes the importance of this tool for reducing early neonatal mortality, 11 17 18 which showed the slowest improvement during the era of the Millennium Development Goals. 39 …”
Section: Discussionmentioning
confidence: 99%
“…In other SCC evaluations, compliance was measured either in terms of completing single checklist items, certain bundles (e.g., before/after birth) or the full checklists over the total number of checklists provided [17][18][19], over the total number of live births [20], or over mothers admitted [15]. Other studies simply asked health care providers whether they carried out essential birth practices outlined in the SCC [21] (Abawollo et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[2] Since then, the SCC has been implemented in many countries and regions, but with inconsistent results. [3][4][5][6] In 2018, our hospital took the lead in introducing and applying the SCC in China based on our experience, and the National Health Commission of China promoted the SCC nationwide. As in some other countries, [6][7][8] we found that providing the checklist only to health care workers or requiring health systems to use the safe delivery checklist does not lead to widespread and sustained use of the checklist, nor does it improve the quality of patient safety.…”
Section: Introductionmentioning
confidence: 99%